Behaviour of Mrigal (Cirrhinus mrigala) Meat Components during the Washing process in the Preparation of Surimi - T.V., Sankar; A., Ramachandran (Fishery Technology, 2025)
To elucidate the effect of washing, on flesh components, mrigal flesh was washed through one, two and three washing cycles.. Washing resulted in absorption of water (1-3%) and loss of fat (49%). 35% loss of soluble protein (SP) was noticed in the first washing itself and the loss is almost equally shared by the sarcoplasmic (18% of SP) and the myofibrillar proteins (17% of SP). The subsequent washings removed small portions of water-soluble sarcoplasmic proteins resulting in the concentration of myofibrillar proteins. 73% of the soluble protein was retained in the flesh after three washing cycles. The protein had undergone marginal conformational changes as reflected by the decrease in the actomyosin Ca2+ ATPase activity. The rheological properties of the washed flesh were, however, significantly better than that of the unwashed mince.